Tolerogenic dendritic cell transfer ameliorates systemic lupus erythematosus in mice - Funes, Samanta Celeste (2019)
Current treatments for systemic autoimmune diseases partially improve the health of patients displaying low pharmacological efficacy and systemic immunosuppression. Here, the therapeutic potential of transferring tolerogenic dendritic cells (tolDCs) generated with heme-oxygenase inductor cobalt (III) protoporphyrin IX (CoPP), dexamethasone and rosiglitazone for the treatment of systemic autoimmunity was evaluated in two murine models of systemic lupus erythematosus (SLE), MRL-Faslpr and NZM2410 mice. Dendritic cells treated ex vivo with these drugs showed a stable tolerogenic profile after lipopolysaccharide stimulation. Regular doses of tolDCs were administered to anti-nuclear antibody-positive mice throughout 60–70 days, and the clinical score was evaluated. Long-term treatment with these tolDCs was well tolerated and effective to improve the clinical score on MRL-Faslpr lupus-prone mice. Additionally, decreased levels of anti-nuclear antibodies in NZM2410 mice were observed. Although tolDC treatment increased regulatory T cells, no significant reduction of renal damage or glomerulonephritis could be found. In conclusion, these results suggest that the transfer of histone-loaded tolDCs could improve only some SLE symptoms and reduced anti-nuclear antibodies. This is the first study to evaluate antigen-specific tolDC administration to treat SLE. Our report strengthens the clinical relevance of tolDC generation with CoPP, dexamethasone and rosiglitazone and the use of these modified cells as a therapy for systemic autoimmunity.